Development of Small Sided Games Training Variations in the Game of Hockey - Adrian, Faldy Subraza; Nurhayati Simatupang; Suprayitno , Suprayitno (UNIB Press, 2024)
This research aims to produce a product in the form of a book about exercise variations of small sided games. The subjects in this study were 10 athletes for small group trials and 20 athletes for large group trials. The product in this research has been designed and then validated by 2 material experts, namely, a material expert, a hockey coach expert and an expert in small sided games hockey. The first stage of the trial showed that the results of the SGDH expert assessment were that a percentage of 81.29% was obtained in the very feasible category. Then the material expert trial obtained a percentage of 77.08% with the appropriate category. The expert trainer trial obtained a percentage of 79.16% in the feasible category. The results of trials on athlete respondents for small groups were carried out on 10 North Sumatran hockey athletes, where a score of 342 was obtained with a percentage of 85.5%, so the Small sided game hockey training product was in the very feasible category. The second stage of the trial showed that the results of the small-sided game hockey expert's assessment were that a percentage of 93.75% was obtained in the very feasible category. Then the material expert trial obtained a percentage of 91.67% with a very feasible category. The hockey coach expert test obtained a percentage of 89.98% with a very feasible category. The results of the large group trial were carried out on the Unimed hockey field where the total score was 718, with a percentage of 89.75% (Very Eligible). Based on the results obtained in the initial group test, main group test and operational tests that have been obtained, training variations are carried out and small sided games hockey can be used.